Variation of optical parameters of multilayer structures with thin silicon layers at laser annealing - Okhrimenko, O.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The experimental data on Raman scattering (RS) and optical absorption in structures with thin silicon layers on various substrates, as well as in multilayer quartz/Si/SiO₂, SiC/Si/SiO₂ and glass/Si₃N₄/Si/SiO₂ structures, are summarized. It is shown that laser annealing on the above structures leads to changes in spectra of RS and optical transmission that can be explained within the critical action model. The value of critical action of laser radiation is determined for the structures studied.